COMMODIFICATION OF AQIQAH SERVICES ON SOCIAL MEDIA - Rina Darojatun; Zaenal Mukarrom (International Conference on Social and Islamic Studies, 2021)
This article focuses on the transformation of religious messages into service products that can be marketed on Instagram, the object of study is messages that contain aqiqah service modification, virtual audiences that interact in the @aqiqohnurulhayat account and aqiqah service partners who work to lead audiences to use the aqiqah services. This research is a qualitative research, conducted by using virtual ethnography method. The result of research explains that commodification of religious rituals in the @aqiqohnurulhayat account is divided into three things; 1) commodification of the meaning of aqiah services which include: delivery of religious messages, price lists for aqiqah services, catering menus and shopee marketplace promotions. 2) commodification of virtual audiences represented by the photos posted, namely: photos and testimonies from celebrities and religious leaders who lead the public in choosing this aqiqah service, memes that are currently viral and promotions of prizes that attract virtual audiences are getting closer to the service. this aqiqah. 3) commodification of aqiqah service partners, contained in photos and videos that invite the public to become aqiqah partners, persuasively the people are lured by halal income, halal products and the ease of running this aqiqah service business account that have experienced acculturation of religious teachings with the rapid development of digital technology that shifts the lifestyle of middle class Muslims in celebrating the presence of children in the family.